Internal variables in dynamics of composite solids with periodic microstructure - Woźniak, Cz. (Archives of Mechanics, 1997)
A new unified micromechanical approach to dynamics of micro-periodic composite solids is formulated. The proposed approach introduces the concept of internal variables in order to describe the effect of the microstructure size on the global body behaviour. It is shown that the evolution equation for internal variables can be obtained without any specification of the material properties of the composite.